The impact of an educational curriculum using delayed feedback according to different times in learning and retaining the skill of shooting at several goals distributed on the field during (30) for cross-ball players ages (13-15 years) - rashed, mohamed; Ghazi, Abdul Wahab (Journal of Physical Education, 2023)
Through the observation of the first researcher, being an international judge, he found that there is a weakness in the shooting skill for beginners, and therefore the researcher decided to put tests and educational units in the shooting accuracy, as the research assumes the existence of statistically significant hypotheses, and its importance lies as a contribution to the development of this skill and its access to advanced stages, where the researchers used The experimental approach, due to its suitability to the nature of the research, and the research sample consisted of 10 players with a pre and posttest for one group, where they were chosen randomly, and the data was processed statistically using the statistical packages for social sciences (spss) in light of the results obtained by the researchers. Learning the shooting skill and mastering it well. He also recommended the need to use delayed feedback at different times, with an increase in the feedback time in the educational units, in order for the player to benefit more from the coach’s instructions..